Focus on Islam and universal brotherhood [videorecording] - Naik, Zakir, 1965-; Islamic Research Foundation; Saba Islamic Media ([Kuala Lumpur] : Saba Islamic Media, 1997)
A talk by Dr. Zakir Naik that focus on Islam and universal brotherhood and address to a non-muslim gathering
Title from title screen
Speaker: Dr. Zakir Naik
Keywords: Islam; Religious life -- Islam